Historic deforestation and the fate of endemic invertebrate species in streams - Jon S. Harding (New Zealand Journal of Marine and Freshwater Research, 2003)
Deforestation is a global phenomenon threatening the biodiversity of many unique forested ecosystems. The volcanic calderas of Banks Peninsula, New Zealand, experienced widespread deforestation from 1860 to 1900 when >98% of the indigenous forest was removed. Streams on the Peninsula possess several regionally‐endemic species. The objective of this study was to assess the effect of historic deforestation on stream faunas by surveying the distribution of endemic and other benthic invertebrate species in relation to remnant and regenerating indigenous forest fragments. Twenty‐seven sites, in nine catchments were surveyed. Three catchments were dominated by forest, three by farmland, and three were predominantly farmland with forested headwaters. Taxonomic richness was significantly greater in forested streams than agricultural streams, particularly for Ephemeroptera, Plecoptera, and Trichoptera taxa. Distributions of the regionally‐endemic hydrobiosid caddisflies Costachorema peninsulae and Edpercivalia banksiensis were restricted to forest fragments. Two other endemics, the stonefly Zelandobius wardi and the caddisfly Hydrobiosis styx , were rarely collected but seemed to be restricted to headwater sites in forest. In contrast, the blepharicerid Neocurupira chiltoni was widely distributed in streams, regardless of land cover, and in relative abundances unrelated to site location within the catchment. Evidence from Banks Peninsula streams suggests that throughout New Zealand a number of species unknown to science may have been lost because of past deforestation, and that remnant forested habitats may be vital to the conservation and preservation of regionally endemic species.